Treatment of the pulp of the immature tooth apexification with Mineral Trioxide Aggregate - Velásquez Reyes, Víctor (2009)
This article reviews main publications about Mineral Trioxide Aggregate (MTA) for its use and application in dental pulp treatments for young permanent teeth (immature apices) such as apexification. First, MTA cement was used to resolve a complication of root perforations, as well as retrograde fillings. Besides, it has features that differentiate it from Portland cement. For choosing treatment for pulpa1 injury in non-vital and vital teeth, we review root formation process from embryological point of view, different stages of root and apical development the immature tooth, comparing them to Nolla's 'stage classification of calcification. Therefore, apexification is a widely used altemative treatment for non-vital pulp, being calcium hydroxide and MTA materials the most common election.Afterwards, when there is formation of new tissue fpr apical closure, conventional root canal treatrnent will be performed.